2010
DOI: 10.1007/s10462-010-9162-1
|View full text |Cite
|
Sign up to set email alerts
|

A biologically inspired object-based visual attention model

Abstract: A biologically inspired object-based visual attention model is proposed in this paper. This model includes a training phase and an attention phase. In the training phase, all training targets are fused into a target class and all training backgrounds are fused into a background class. Weight vector is computed as the ratio of the mean target class saliency and the mean background class saliency for each feature. In the attention phase, for an attended scene, all feature maps are combined into a top-down salien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Understanding gist recognition in humans and replicating this ability in computers has been an ongoing research goal (Fei-Fei et al 2007b;Loschky et al 2007;Wei et al 2010;Walther et al 2011;Lee and Choo 2013;Linsley and MacEvoy 2014;Malcolm et al 2014). In the early psychovisual studies, Potter found that a scene is processed rapidly at an abstract level before intentional selection occurs (Potter 1975).…”
mentioning
confidence: 99%
“…Understanding gist recognition in humans and replicating this ability in computers has been an ongoing research goal (Fei-Fei et al 2007b;Loschky et al 2007;Wei et al 2010;Walther et al 2011;Lee and Choo 2013;Linsley and MacEvoy 2014;Malcolm et al 2014). In the early psychovisual studies, Potter found that a scene is processed rapidly at an abstract level before intentional selection occurs (Potter 1975).…”
mentioning
confidence: 99%